PEOPLE’S RIGHTS IN THE 1946 CONSTITUTION AND THE DEVELOPMENT OF THE 2013 CONSTITUTION IN VIET NAM - Hang, Nguyen Thi Thu (IJRDO- Journal of Educational Research, 2019)
The 1946 Constitution, the first constitution in our history which was approved on November 09, 1946 by the National Assembly of Democratic Republic of Vietnam included 7 Chapters and 70 Articles. The 1946 Constitution was a democratic and advanced constitution which was the optimal result of national and international values, clearly shown in Ho Chi Minh’s perspective in ‘Legality and Humanity’. It met the desire of national independence and territorial integrity. One of the fundamental contents of this Constitution was the regulations on basic rights of people - the core value that the next constitutions inherit. Legality development in Vietnam is associated with the development and completion of the socialist legal government which is marked by the creation of different constitutions. The common characteristic of the 1964 Constitution, 1959 Constitution, 1980 Constitution, 1992 Constitution, and 2013 Constitution is that the declaration on human rights is the basic foundation to build Vietnam laws in which the statements in the 1946 constitution is the foundation that is adopted in the next constitutions.